2009
DOI: 10.1182/blood-2009-03-213850
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent adult progenitor cells can suppress graft-versus-host disease via prostaglandin E2 synthesis and only if localized to sites of allopriming

Abstract: IntroductionThe wider application of bone marrow transplantation (BMT) has been limited, in part, by graft-versus-host disease (GVHD) complications. Human and mouse mesenchymal stem cells (MSCs) have been shown to suppress allogeneic-induced and nonspecific mitogen-induced T-cell proliferation in vitro (reviewed in detail 1,2 ). Implicated suppressive mechanisms have included interleukin (IL)-10, 3 transforming growth factor (TGF)-␤, hepatocyte growth factor, 4 indoleamine 2,3 dioxygenase (IDO), 5 nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 47 publications
6
73
1
Order By: Relevance
“…This result aligns with several reports highlighting that MSC-mediated suppression can occur via the IDO pathway downstream of licensing signals (e.g., IFN-g) and supports the notion that MAPCs would be most suppressive in the context of an inflammatory environment/ongoing immune response (41). Consistent with this, rodent MAPCs were shown to exhibit efficacy in the context of graft-versus-host disease only when present at sites of allopriming (36). Although implicated in MSC-mediated T cell suppression, we did not observe a role for PGE 2 in MAPC-mediated T cell suppression under any stimulation conditions.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This result aligns with several reports highlighting that MSC-mediated suppression can occur via the IDO pathway downstream of licensing signals (e.g., IFN-g) and supports the notion that MAPCs would be most suppressive in the context of an inflammatory environment/ongoing immune response (41). Consistent with this, rodent MAPCs were shown to exhibit efficacy in the context of graft-versus-host disease only when present at sites of allopriming (36). Although implicated in MSC-mediated T cell suppression, we did not observe a role for PGE 2 in MAPC-mediated T cell suppression under any stimulation conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Human MAPCs can be distinguished from human MSCs on the basis of cell surface phenotype, cell size, transcriptional profile, cytokine production, differentiation potential and replicative capacity (6, 10, 34, 35). Previous work showed that murine MAPCs exert therapeutic immunomodulatory effects in the context of graft-versus-host disease prophylaxis, in MLR systems in vitro, and that human MAPCs prevented inflammation in a murine model of stroke, supporting a role for these cells in treating human immune-mediated diseases (36)(37)(38).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We measured the proinflammatory cytokines IL-6 and TNF-α and the regulatory cytokines IL-10, TGF-β 1 , TGF-β 2 and TGF-β 3 using multiplex bead-based technology in commercially available kits (Fluorokine MAP; R&D Systems, Wiesbaden, Germany) [21][22][23]. To measure systemic concentrations of the anti-inflammatory cytokine IL-1RA, we used commercially available ELISA kits (Quantikine ELISA kits; R&D Systems).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, similar to MSC, MAPC also seem to have immunesuppressive capacity, which may be favorable in an allogeneic setting. 112,113 Despite their large expansion capacity, no karyotypic instabilities have been reported for human MAPC. Our recent data reveal that MAPC transplantation improves wound vascularization as well as reepithelialization in a full-thickness wound model in immunedeficient mice (unpublished results) ( Table 1).…”
mentioning
confidence: 99%